A Study Of Integrated CAD/CAM System With CNC Desktop Machine - Chik, Nur Aishah (Universiti Sains Malaysia, 2018)
Integration of CAD/CAM has significantly increased the efficiency and performance of CNC machining. Complex part can be designed quicker and accurately with software that enables the user to visually see the part and its dimensions using CAD. CAM packages allow these complex parts to be brought to life by calculating tool path and writing the code to manufacture the part on a Computer Numerical Controlled (CNC) machine that called G-code. The CNC Desktop milling machine created to allow the machining at small level. To improve the limitation and machining process of CNC Desktop milling machine, the few component are added into the machining controller that is spindle speed controller that activate the M03 code for spindle on and off and S code for the speed. The important of CAD/CAM in CNC machining are shown in this project by creating simulations for machining in FUSION360. The simulations are to verify the toolpath for machining and generate a G-code that used to control the CNC machine. An open pocketing modeling were created as the part for the experiment to verify the importance of the parameter that set in machining focusing on the spindle speed variation using surface roughness test. From the surface roughness test, the surface roughness is increased with the decreasing of the spindle speed. A set of parameter for 1200 RPM used as the reference for comparison .The percentage of the improvement on surface roughness if the maximum spindle speed, 2000RPM used is increase by 8.09% while when minimum spindle speed used for experiment, 400RPM the surface roughness increase significantly to 40.42% showed that the higher spindle speed with lower feed rate provide much better result for surface roughness quality.